Review on molecular biological approaches to investigate the effect of endurance training - Seo, T.-B.; Kim, Y.-S. Youn, S.-W.; Oh, M.-J.; Seo, J.-H.; Park, H.-C. (International Journal of Applied Sports Sciences, 2014)
The purpose of this study is to examine details of domestic and foreign papers that verified the effect of endurance training using molecular biological approaches and to investigate the directivity of molecular biological study, analytical technology and analytical factors for the analysis of training effects. Existing domestic and foreign papers on endurance training that investigated the effect of training based on molecular biological analysis of human beings were reviewed. In order to increase reliability of the selected papers and their compatibility with the purpose of this study, the papers were reclassified by a group of experts that consisted of physical education professors and doctors of exercise physiology. The final papers selected were studied for the change in hormones and enzymes through blood and muscular tissues based on study topic and trend analysis from a macroscopic perspective. Analytical methods used include western blot, RT-PCR, ELISA and immunohistochemistry of molecular biology. Analytical variables investigated / analyzed were ACE, ACTN, PPARs, UCP, mitochondrial DNA variant, creatine kinase, renin-angiotensin, AMPK for blood and COX, myosin binding protein C fast-type, glycogen phosphorylase, pyruvate kinase, GLUT, PPARs, and AMPK for muscle. Such molecular biological analytical techniques and variables should be widely used to provide 1) conditioning of professional athletes and life sports athletes, 2) analysis of training effect, and 3) scientific and future-oriented methods for health enhancement.